An Augmented Negative Force-Frequency Relationship and Slowed Mechanical Restitution Are Associated With Increased Susceptibility to Drug-Induced Torsade de Pointes Arrhythmias in the Chronic Atrioventricular Block Dog - Sprenkeler, David J.; Bossu, Alexandre; Beekman, Jet D. M.; Schoenmakers, Marieke; Vos, Marc A. (Frontiers in Physiology, 2018)
Introduction In the chronic AV-block (CAVB) dog model, structural, contractile and electrical remodeling occur, which predispose the heart to dofetilide-induced Torsade de Pointes (TdP) arrhythmias. Previous studies found a relation between electrical remodeling and inducibility of TdP, while structural remodeling is not a prerequisite for arrhythmogenesis. In this study, we prospectively assessed the relation between in vivo markers of contractile remodeling and TdP inducibility. Methods In 18 anesthetized dogs, the maximal first derivative of left ventricular pressure (LV dP/dtmax) was assessed at acute AV-block (AAVB) and after two weeks of chronic AV-block (CAVB2). Using different pacing protocols, three additional markers of contractile remodeling, i.e. force-frequency relationship (FFR), mechanical restitution (MR) and post-extrasystolic potentiation (PESP) were determined. Infusion of dofetilide (0.025 mg/kg in 5 minutes) was used to test for TdP inducibility. Results After infusion of dofetilide, 1/18 dogs and 12/18 were susceptible to TdP-arrhythmias at AAVB and CAVB2, respectively (p = 0.001). The inducible dogs at CAVB2 showed augmented contractility at low stimulation frequency (2354 ± 168 mmHg/s in inducible dogs versus 1091 ± 59 mmHg/s in non-inducible dogs, p < 0.001) with a negative FFR, while the non-inducible dogs retained their positive FFR. The time constant of the MR curve was significantly higher in the inducible dogs (158 ±7 ms vs 97±8 ms, p < .0001). Furthermore, a linear correlation was found between a custom-made score of the number and severity of arrhythmias and contractile parameters, i.e. contractility at low stimulation rate (r = 0.73, p = 0.002), the slope of the FFR (r = -0.58, p = 0.01) and the time constant of MR (r= 0.66, p = 0.003). Thus, more severe arrhythmias were seen in dogs with the most pronounced contractile remodeling. Conclusion Contractile remodeling is concomitantly observed with susceptibility to dofetilide-induced TdP-arrhythmias. The inducible dogs show augmented contractile remodeling compared to non-inducible dogs, as seen by development of a negative FFR, higher maximal response of MR and PESP and slowed MR kinetics. These altered contractility parameters could reflect disrupted Ca2+ handling and Ca2+-overload, which predispose the heart to delayed- and early afterdepolarizations that could trigger TdP-arrhythmias.